Técnicas de bioinformática aplicadas ao estudo de poligalacturonases de fungos - Santos, Adriana Miranda dos (Universidade Federal de São Carlos, 2012)
Plant cell walls are composed of approximately 65% cellulose microfibrils and pectin. The latter is proteolytically degraded by the so-called pectinases enzymes (also known as pectinolytic enzymes). Pectinases may be either depolymerizing. They are produced by plants, filamentous fungi, bacteria, and yeast. Due to the wide commercial use of pectinase, one has testified a growing number of studies devoted to understand the activities of such enzymes. Bioinformatics tools were employed throughout this work in order to study fungal polygalacturonase (PG) under two aspects. Firstly, all stored fungal PG sequences in databases (2093) were analyzed in order to evaluate through searching for sequential motifs and phylogenetic studies the possibility to classifying the enzymes as either Endo- or Exo-PG. After excluding those with less than 70 amino acids, those that corresponded to the hypothetical protein , and those that were neither PG nor fungal PG, there were 957 sequences left. Those sequences were separated according to genus and species. For each group, multiple sequence alignments were made by using ClustalW software. The alignments were analyzed and the sequences displaying 100% identity were then expunged, thus resulting in a database of unique sequences of fungal PG. By means of the alignment, the study of structural motifs, and the construction of phylogenetic trees, one was able to classify all the sequences according to their mode of action in either Endo- or Ex-PG. Throughout the second part of our research, protein homology-modeling methods were employed while constructing a three-dimensional model of a L. gongylophorus fungal polygalacturonase, symbiont of leaf-cutting ant. The model was validated by PROCHECK, VERIFY 3D, and WHAT IF software. By analyzing the 3D model of the L. gongylophorus PG, a catalytic mechanism of the enzyme was outlined, which may take place by inverting the configuration of sugar anomeric carbon (substrate).
Keywords: Química orgânica; Poligalacturonase; Fungos; Alinhamento de sequências; Sequência de aminoácidos; Relações filogenéticas; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA